2021
DOI: 10.7759/cureus.13089
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Ectopic Mindedness: Scar Ectopic Pregnancy, a Diagnostic Dilemma

Abstract: There has been a consistent rise in ectopic pregnancies due to increase in maternal age, infertility treatment, cesarean sections, smoking among women, and use of contraceptives. With the extratubal ectopic pregnancies accounting for only 4% of the total ectopic pregnancies, scar pregnancies are even more of a rare entity with their incidence being less than 1%. We hereby present two cases of ectopic pregnancies, which though managed successfully presented a huge diagnostic challenge in the first case while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…About 2.5% occur in the cornua of the uterus, and the abdominal cavity, cervix, and ovaries account for 1.5% of ectopic pregnancies [ 18 ]. Further, with rates of cesarean sections increasing, it has been reported that the scar left behind from the hysterotomy can serve as a possible implantation site, accounting for 1% of ectopic pregnancies [ 19 ].…”
Section: Reviewmentioning
confidence: 99%
“…About 2.5% occur in the cornua of the uterus, and the abdominal cavity, cervix, and ovaries account for 1.5% of ectopic pregnancies [ 18 ]. Further, with rates of cesarean sections increasing, it has been reported that the scar left behind from the hysterotomy can serve as a possible implantation site, accounting for 1% of ectopic pregnancies [ 19 ].…”
Section: Reviewmentioning
confidence: 99%
“…Older maternal age may also increase the risk of scar ectopic pregnancy due to the higher prevalence of uterine fibroids and other conditions that can cause uterine scarring [13]. It is important to note that, while these factors increase the risk of scar ectopic pregnancy, the condition can still occur in women without any known risk factors [14]. Therefore, a high index of suspicion is necessary in any woman with a previous uterine surgery who presents with symptoms of ectopic pregnancy [15].…”
Section: Introductionmentioning
confidence: 99%